A phenominal study of recidivism among the youth incarcerated at Polokwane Secure Care Centre, Limpopo Province - Tjikana, Katlego Lerato (My University, 2018)
The study explored recidivism as a lived experience among the youth incarcerated at Polokwane Secure Care Centre in Polokwane, Limpopo Province. The study focused on describing the subjective meanings that recidivist youth attach to their behaviour and established what the youth consider to be the causes of their recidivist behaviour. Furthermore, the study explored what the youth perceive as possible interventions to reduce recidivism. A total of six participants (all males; aged between 16 and 18) were selected using the purposive sampling method. Data were collected using semi structured interviews. Thematic analysis method was used to analyse the data. The six major themes that emerged during data analysis were; a) labelling; b) peer pressure; c) substance abuse; d) socialisation; e) conduct disorder; and f) self discipline and constructive activities. The findings of the study suggest that various factors contribute to recidivism including the use of substances; parenting styles as well as peer pressure. Furthermore, the findings showed that behavioural problems including criminal behaviour in the youth, may be due to being labelled as a criminal or Conduct Disorder. The findings further suggest the influence the environment has on the youth, and how being socialised in an environment that emphasises a fancy lifestyle may contribute to the youth engaging in criminal activities to meet the standards of that particular environment. The findings further suggest that self discipline and of constructive activities may help to reduce recidivism among the youth. The study is concluded by, among others, recommending that psychological services be widely available to communities which will allow the youth to have easy access to such services. This may assist them in dealing with issues such as their experiences within the households (such as abuse) and how to better manage/ control their emotions as opposed to responding aggressively.
Thesis(M.A. (Clinical Psychology)) -- University of Limpopo, 2018
Keywords: Recidivism; incarcerated; Youth; Behaviour; Psychological services; Prisoners; Ex- convicts; Recidivism